PENGARUH INFLASI DAN SUKU BUNGA TERHADAP HARGA SAHAM PERUSAHAAN SEKTOR PROPERTI & REAL ESTATE DI BURSA EFEK INDONESIA - Anna Wulandari; Meli Andriani (Jurnal Manajemen Kewirausahaan, 2016)
Inflation and interest rates are the two factors of several factors thought to have a major influence on the price of the shares of Property and Real Estate Industry. To prove the influence of these two factors, the research conducted in order to know the effect of inflation and interest rates on the price of the shares of Property and Real Estate Industry.The study was conducted in Property and Real Estate Industry to retrieve data on the share price of 2013-2015 in Jakarta as a sample to be calculated. The data used in this research is secondary data. Secondary data is data obtained or collected researchers from existing sources. Simple and multiple regression analysis is used as a tool of analysis.This study resulted in three main findings refer to the hypothesis, namely: 1) Inflation has a positive effect on stock prices; 2) The interest rate has a negative effect on stock prices: 3) inflation and interest rate have effect on stock prices.Based on these findings it is suggested to increase the stock price so do efforts to improve internal financial management taking into account external factors.Â Keywords: Inflation, interest rates, stock price